2001
DOI: 10.1038/labinvest.3780303
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Inflammatory Protein-1α Relates to the Recruitment of Inflammatory Cells in Myosin-Induced Autoimmune Myocarditis in Rats

Abstract: SUMMARY:In experimental autoimmune myocarditis (EAM) there is a characteristic initial focal inflammatory response in the myocardium, induced mainly by CD4 ϩ T cells and macrophages, which leads to massive myocardial damage. Macrophage inflammatory protein-1␣ (MIP-1␣) induces chemotaxis in lymphocytes, eosinophils, basophils, and macrophages. We assessed the potential role of MIP-1␣ in the pathogenesis of EAM in rats immunized with porcine myosin. Following immunization, the levels of MIP-1␣ mRNA in EAM showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…[22][23][24]37 In the present study the cardiac expression of MIP-1␣ and MIP-2 was markedly suppressed by rhTRX-1. Our study showed that serum MIP-2 levels in mice with EAM were not significantly different from those of controls, which was inconsistent with previous reports that plasma MIP-2 levels were significantly elevated in CVB3 myocarditisinfected mice on days 7, 10, and 14.…”
Section: Discussionmentioning
confidence: 62%
“…[22][23][24]37 In the present study the cardiac expression of MIP-1␣ and MIP-2 was markedly suppressed by rhTRX-1. Our study showed that serum MIP-2 levels in mice with EAM were not significantly different from those of controls, which was inconsistent with previous reports that plasma MIP-2 levels were significantly elevated in CVB3 myocarditisinfected mice on days 7, 10, and 14.…”
Section: Discussionmentioning
confidence: 62%
“…We previously demonstrated that MIP-1α mRNA and protein are highly expressed in the hearts of rats with EAM from day 11 after first immunization. 57 Th1 cells produce interferon-γ (IFN-γ), which is mainly involved in cell-mediated immune responses, whereas Th2 cells produce IL-4, IL-5, IL-6, IL-10 and IL-13, which participate in humoral responses. Immune dysfunction associated with autoimmune disease is known to involve an imbalance between Th1 and Th2 cells.…”
Section: Pparγ and Myocarditismentioning
confidence: 99%
“…57 The onset of EAM in rats occurs approximately 2 weeks after the first immunization with porcine cardiac myosin. At this time, small numbers of CD4 + T cells and macrophages start to infiltrate into the myocardium and various cytokines are expressed.…”
Section: Pparγ and Myocarditismentioning
confidence: 99%
“…Many studies have demonstrated that nuclear factor kappa-B (NF-κB)-induced proinflammation may play an important role in the development of this disease [4,5], during which many proinflammatory cytokines such as interleukin-6 (IL-6) and monocyte chemotactic protein-1 (MCP-1) are released, and the direct result is necrosis of myocytes. Various immune cells are also recruited to the lesion tissue to amplify the inflammatory reaction during myocarditis [6]. …”
Section: Introductionmentioning
confidence: 99%